Phenotypic presentation trends of transthyretin amyloid cardiomyopathy: are we getting better?. (14th October 2021) - Chandrashekar, P; Rashdan, L; Dale, Z; Warner, S; Gill, S; Fischer, K; Kim, M; Nazer, B; Masri, A
Abstract: Introduction: Transthyretin amyloid cardiomyopathy (ATTR-CM) is being increasingly recognized due to recent advances in non-invasive imaging notably bone scintigraphy and newer effective therapies - particularly tafamidis, which was shown to improve survival and decrease heart failure hospitalizations in the ATTR-ACT trial. Earlier tafamidis use appeared to be more beneficial, as reflected by NYHA class I and II patients being associated with lower mortality and hospitalizations compared to NYHA class III. Increased awareness will likely lead to an increasing number of ATTR-CM patients being diagnosed with concerns regarding applicability of ATTR-ACT criteria on these patients. Purpose: To investigate ATTR-CM phenotypic presentation trends based on initial clinical, biomarkers and transthoracic echocardiographic (TTE) data. Methods: From 2005–2020, 116 ATTR-CM patients were seen at our amyloidosis center, who were stratified into 3 time periods based on the date of diagnosis: Early (21 patients, pre-2016), Mid (46 patients, 2016–2018), and Recent (49 patients, 2018–2020). ATTR-CM diagnosis was established based on the standard criteria of confirmed ATTR variant + typical TTE features; histological confirmation endomyocardial biopsy; or typical diffuse cardiac tracer uptake on bone scintigraphy while ruling out light chain amyloidosis. With less typical imaging, cardiac MRI typically served as a confirmatory test prior to pursuing histological confirmation. Demographics, cardiac biomarkers, diagnostic method used, and TTE variables that raise the suspicion of ATTR-CM were compared across time periods using one-way ANOVA test and Fischer's exact test. Results: There was a significant change in the predominant method of diagnosis with the majority of patients in the Early time period diagnosed by endomyocardial biopsy, whereas in the Recent time period the majority of patients were diagnosed via pyrophosphate scintigraphy (Figure). Despite increasing number of patients being diagnosed, the clinical phenotype at diagnosis did not change significantly with similar proportion of patients NYHA class I/II, median daily diuretic dose, biomarkers, having at least one heart failure hospitalization prior to diagnosis, and similar TTE phenotype (Table). Only the age at diagnosis significantly increased across time periods. Women represented the minority of patients across all time periods. Conclusion: Despite the increased awareness of ATTR-CM, there have been no major changes in the clinical, cardiac biomarker, or TTE phenotype on presentation in patients referred to our center for suspicion or a diagnosis of ATTR-CM. Our findings challenge the assumption that patients with ATTR-CM are being identified earlier with milder phenotypes. Women with ATTR-CM likely remain largely undiagnosed in our community. Continued education and knowledge dissemination are essential to identify ATTR-CM patients earlier to achieve better outcomes in this population. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Pranav Chandrashekar is supported by an educational grant from Pfizer, Inc paid to Oregon Health and Science University.